Students' Social Care During the COVID-19 Pandemic: How Do School and Family Make Collaboration to Develop it? - Aziz, Rahmat; Novezry, Ai Rinda; Siswoyo, Selina Rahmawati; Mustofa, Mohammad Hasan; Hady, M. Samsul (LPPM Undiksha, 2021)
Learning during the COVID-19 pandemic has caused difficulties that have not been resolved by the school and family, failing to develop social care characters in students. The presence of teachers who are not ready to teach online due to inadequate abilities and facilities Learning activities to develop Students' Social Care during the COVID-19 period have created various difficulties for teachers, parents, and students. Challenges that are not responded to appropriately by schools and families have resulted in low social care characteristics. This paper aimed to describe the social care character of students and analyzed the role of schools (teachers) and families (parents) during the learning process. This paper is research on data collected through an open questionnaire and online interviews. An open questionnaire was given to 24 students from three high schools in Malang, East Java Province. In addition, data were also obtained from ten teachers and nine parents. Teachers and parents have difficulty developing social care characters, resulting in the students' low social care character. The selection of the suitable learning model during the pandemic and harmonious cooperation between schools and families become a determinant of success in the learning process of students' social care characters. Thus, the online learning process should change the mindset of teachers and parents that the teacher-centred learning process is not suitable for a student-based learning process as learning actors who have the authority to seek and produce knowledge.